2009
DOI: 10.1007/s11596-009-0327-6
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive neuronavigator-guided microsurgery and photodynamic therapy for gliomas

Abstract: In order to evaluate the effectiveness of neuronavigator-guided microsurgery and keyhole technique for the resection of gliomas, a total of 60 patients with gliomas were exactly located by using neuronavigator during microsurgery. Forty deep-seated gliomas were resected through a keyhole operative approach. Thirty out of the 60 cases were subjected to photodynamic therapy (PDT) after tumor resection. The therapeutic effectiveness of all the cases was recorded and analyzed. The results showed that glioma was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…These early phase studies suggested a survival advantage for test arms compared to controls. However, side effects after PDT were severe and included deep venous thrombosis, neurological deficits, and multi-organ failure [33,35,53,73]. Although PDT was perhaps effective, it is very difficult to distinguish whether reported side effects are caused by the surgery or the PDT, or simply complications of the disease itself.…”
Section: Challenges For Development Of Pdt For Gbmmentioning
confidence: 99%
“…These early phase studies suggested a survival advantage for test arms compared to controls. However, side effects after PDT were severe and included deep venous thrombosis, neurological deficits, and multi-organ failure [33,35,53,73]. Although PDT was perhaps effective, it is very difficult to distinguish whether reported side effects are caused by the surgery or the PDT, or simply complications of the disease itself.…”
Section: Challenges For Development Of Pdt For Gbmmentioning
confidence: 99%
“…Rebleeding rate in group B (1.1%) was significantly lower than that in group A (9.1%). It suggested that sucking too big volume of clots in a short time would be more favorable (29). In light of this, we conducted this research.…”
Section: Tang Zp Et Al: Modifying the Details Of Aspiration In Patiementioning
confidence: 97%
“…Due to powerful data processing capacity, GM (1,1) model has been widely used in many sectors of national economy, and its study is prosperity. Usually, we choose the least squares method to process GM (1,1) [1][2][3], but literatures [4][5][6] suggest least absolute estimation. So,it has some positive meaning to study their precisions of the two methods in the paper.…”
Section: Introductionmentioning
confidence: 99%
“…So,it has some positive meaning to study their precisions of the two methods in the paper. Literature [4] and [5] are based on original observation datum and their predicted datum,but there is difference. Literature [6] is based on original observation datum and their estimation datum.Observation 's predicted datum are not observation's estimation datum.…”
Section: Introductionmentioning
confidence: 99%